Burnout syndrome and work engagement in nursing staff: a systematic review and meta-analysis - Vargas-Benítez, Miguel Ángel; Izquierdo-Espín, Francisco José; Castro-Martínez, Nuria; Gómez-Urquiza, José L.; Albendín-García, Luis; Velando-Soriano, Almudena; Cañadas-De la Fuente, Guillermo A. (Frontiers in Medicine, 2023)
Background: A difficult and demanding work environment, such as that often experienced in healthcare, can provoke fatigue, anxiety, distress and discomfort. This study considers factors that may influence levels of burnout and work engagement among nurses, and seeks to determine the relationship between these conditions. Method: A systematic scoping review was performed, in accordance with the PRISMA Extension for Scoping Reviews, based on data obtained from a search of the PubMed/MEDLINE and Scopus databases carried out in 2022 using the search equation: “work engagement AND nurs* AND burnout”. This search identified nine quantitative primary studies suitable for inclusion in our analysis. Results: Work overload, type of shift worked and/or area of hospital service, among other elements, are all relevant to the development of burnout. This syndrome can be countered by social support and appropriate personal resources and values, which are all positively associated with work engagement. Our analysis revealed a significant correlation between work engagement and the different domains of burnout. The correlation effect size between burnout and work engagement was -0.46 (95% CI -0.58, -0.31), with p<0.001 Conclusion: Well-targeted interventions in the healthcare work environment can reduce burnout levels, strengthen work engagement and enhance the quality of healthcare.